Rates of leaf fall and nutrient recycling of shade trees in coffee (Coffea arabica L.), cardamom (Elettaria cardamomum Maton) and black pepper (Piper nigrum L.) pro- duction systems of Mudigere, Karnataka - J Babitha, M Dinesh Kumar (Journal of Spices and Aromatic Crops, 2006)
The rates of leaf fall and nutrient addition by different shade trees in coffee (Coffea arabica),cardamom (Elettaria cardamomum) and black pepper (Piper nigrum) production systems weredetermined at Mudigere (Karnataka). Most trees shed leaves during September to December.Highest leaf shed (4214.5 g m-2 year-1) was noticed in Artocarpus integrifolia followed by Ficustjahela (3976.2 g m-2 year-1). Nitrogen concentration of the leaves varied from 0.21% (Dalbergialatifolia) to 1.89% (Albizia lebbeck); phosphorus concentration from 0.01% (Holigarna arnottiana)to 0.11% (Pongamia pinnata); and potassium concentration from 0.21% (H. arnottiana) to 1.52%(Lagerstroemia lanceolata). In coffee production system, A. integrifolia recorded highest contentof nitrogen (39.19 g m-2 year-1) while F. tjahela recorded higher phosphorus (2.07 g m-2 year-1)and potassium (34.99 g m-2 year-1) contents. In cardamom production system, Erythrina indicarecorded higher contents of nitrogen (25.72 g m-2 year-1) and phosphorus (1.62 g m-2 year-1)while L. lanceolata contained more potassium (14.11 g m-2 year-1). In black pepper productionsystem, Michelia champaca recorded higher contents of nitrogen (31.11 g m-2 year-1), phospho-rus (3.46 g m-2year-1) and potassium (29.95 g m-2 year-1). Species that were rich in nitrogencontent had initial lower (< 30) C/N ratio. Lignin content varied from 17.3% to 25.3% andcellulose from 4.4% to 10.1% in various tree species.